Effet d'un mélange des huiles essentielles commerciales sur certains paramètres biochimiques et le poids corporel de cailles des blés (Coturnix coturnix) traitées par l'insecticide Karaté - Dahoui Manel; Tlailia Akram Saber (My University, 2024)
The objective of this study is to contribute to the determination of the effects of repeated exposure to the commercial insecticide Karate (active ingredient lambda-cyhalothrin 50 g/L) and the potential protective role of the mixture of two commercial oil extracts, mug wort and thyme, on body weight and selected blood plasma biochemical parameters (protein, glucose, triglycerides and cholesterol) in quail. Four groups of birds were treated daily with (0.5 ml) of Karate insecticide and commercial mixture of mug wort oil and thyme for 10 days according to the following experimental principle: Group (01): Control. Group (02): Treated with the dose (1/30 LD50 birds) of the commercial pesticide "Karate". Group (03): Treated with the dose (1/30 LD50 birds) of the commercial pesticide "Karate" + mixture of mug wort and thyme oils. Group (04): Treated with the dose (1/90 LD50 birds) of the commercial pesticide "Karate" and Group (05): Treated with the dose (1/90 LD50 birds) of the commercial pesticide "Karate" + mixture of mug wort and thyme oils. The results showed the following: A significant decrease in body weight in males in group (02) and not significant for males in groups (03), (04) and (05) compared to the control group, and a non-significant disturbance (increase and decrease) between treatment groups. A significant decrease for females in both groups (03) and (04) compared to the control group, as well as between the two groups (02) and (03). A non-significant decrease in plasma protein concentrations in males in both groups (02) and (04) and a non-significant increase in males in both groups (03) and (05) compared to the control group. A significant increase for males in group (04) compared to group (05), a non-significant decrease in glucose concentrations in males in both groups (02) and (03), a non-significant increase for both groups (04) and (05) compared to the control group, and they were not significantly disturbed between the treated groups. Significant decrease in females in the fifth group and not significant for both groups (02) and (03) and a non-significant increase for group (04) compared to the control group and a significant decrease for group (05) compared to group (03). A non-significant decrease in triglyceride concentrations in males in groups (02), (04) and (05) as well as in females in both groups (02) and (04) and while it was not significantly increased for males in the third group and females in both groups (03) and (05) compared to these control groups and a non-significant disturbance between the treated groups. A non-significant decrease in cholesterol concentrations in males in group (02) and they were not significantly increased for groups (03), (04) and (05) compared to the control group and its non-significant disturbances between the treated groups. As well as these decreases for females of both groups (02) and (05) and its increases for females of groups (03) and (04) compared to the control group and its significant decrease in group (03) compared to group (05) ----------------------------------------------------------------------------------------------------------------------------------- الهدف من هذه الدراسة هو المساهمة في تحديد الآثار الناجمة عن التعرض المتكرر للمبيد الحشري التجاري 'كاراتي' (المادة الفعالة لمبدأ سيالوهثرين 50 غ/ل) وعلى الدور الوقائي المحتمل لخليط مستخلصي الزيتين التجاريين الشيح والزعتر على وزن الجسم، وعلى مستويات بعض المعايير البيو كيميائية في بلازما الدَّم؛ البروتينات، الغلوكوز الدهون الثلاثية والكوليسترول) عند طيور سمان القمح. تم تزقيم (0.5 مل) يوميًا من المبيد الحشري 'كاراتي' ومن مبيد كاراتي وخليط زيتي الشيح والزعتر التجاري لأربعة أفواج من الطيور مدة 10 أيام وفقا للمبدأ التجريبي التالي: الفوج (01): شاهد. الفوج (02): معامل بالجرعة 1/30 من الجرعة القاتلة ل 50 % من الطيور من المبيد التجاري 'كاراتي'. الفوج (03): معامل بالجرعة 1/30 من الجرعة القاتلة ل 50 % من الطيور من المبيد التجاري 'كاراتي' + خليط زيتي الشيح والزعتر). الفوج (04): معامل بالجرعة 1/90 من الجرعة القاتلة ل 50 % من الطيور من المبيد التجاري 'كاراتي'. الفوج (05): معامل بالجرعة 1/90 من الجرعة القاتلة ل 50 % من الطيور من المبيد التجاري 'كاراتي' + خليط زيتي الشيح والزعتر). أظهرت النتائج المتحصل عليها ما يلي: انخفاضا معنويا في وزن الجسم عند ذكور الفوج (02) وغير معنوي في الأفواج (03)، (04) و (05) مقارنة بالفوج الشاهد، واضطراب (ارتفاع وانخفاض) غير معنوي مقارنة الأفواج المعاملة فيمَا بينها، كذلك انخفاضه المعنوي عند إناث الفوجين (03) و (04) مقارنة بالفوج الشاهد وكذلك بين الفوجين (02) و (03). انخفاض غير معنوي في تركيزات البروتينات البلازمية في الفوجين (02) و(04) وارتفاعها غير المعنوي في الفوجين (03) و (05) عند كل من الذكور والإناث مقارنة بالفوج الشاهد وارتفاعها معنويًا مقارنة بين ذكوروالفوجين (04) و (05). انخفاض غير معنوي في تركيزات الغلوكوز عند ذكور الفوجين (02) و (03) وارتفاعها غير المعنوي عند الفوجين (04) و (05) مقارنة بالفوج الشاهد واضطراباتها غير المعنوية بين الأفواج المعاملة. انخفاضها المعنوي عند إناث الفوج (05) وغير المعنوي عند الفوجين (02) و (03) وارتفاعًا غير معنوي عند الفوج (04) مقارنة بالفوج الشاهد وانخفاضها المعنوي عند الفوج (05) مقارنة بالفوج (03). انخفاض غير المعنوي في تركيزات الدهون الثلاثية عند ذكور الأفواج (02)، (04) و (05) وكذلك عند إناث الفوجين (02) (04) وارتفاعها غير المعنوي عند ذكور الفوج (03) وإناث الفوجين (03) و (05) مقارنة بالفوج الشاهد لكل منهما والاضطراب غير المعنوي مقارنة الأفواج المعاملة فيمَا بينها. ----------------------------------------------------------------------------------------------------------------------------------- L'objectif de cette étude est de contribuer à la détermination des effets d'une exposition répétée à l'insecticide commercial Karaté (matière active lambda-cyhalothrine 50 g/l) et du rôle protecteur possible du mélange de deux extraits d'huile commerciale, l'armoise et le thym, sur le poids corporel et certains paramètres biochimiques de plasma sanguin (protéines, glucose, triglycérides et cholestérol) chez les cailles de blé. Quatre groupes d'oiseaux ont été traités quotidiennement par (0,5 ml) d'insecticide Karaté et de mélange commercial d'huile d'armoise et de thym pendant 10 jours selon le principe expérimental suivant : Groupe (01) : Témoin. Groupe (02) : Traité par la dose (1/30 DL50 oiseaux) de pesticide commercial "Karaté". Groupe (03) : Traité par la dose (1/30 DL50 oiseaux) de pesticide commercial "Karaté" + mélange des huiles d'armoise et de thym. Groupe (04) : Traité par la dose (1/90 DL50 oiseaux) de pesticide commercial "Karaté". Groupe (05) : Traité par la dose (1/90 DL50 oiseaux) de pesticide commercial "Karaté" + mélange des huiles d'armoise et de thym. Les résultats obtenus ont montré ce qui suit : Une diminution significative du poids corporel chez les mâles du groupe (02) et non significative pour les mâles des groupes (03), (04) et (05) comparés au groupe témoin, et une perturbation (augmentation et diminution) non significative entre les groupes traités. Une diminution significative pour les femelles des deux groupes (03) et (04) comparés au groupe témoin, ainsi qu'entre les deux groupes (02) et (03). Une diminution non significative des concentrations des protéines plasmatiques chez les mâles des deux groupes (02) et (04) et une augmentation non significative pour les mâles des deux groupes (03) et (05) comparés au groupe témoin. Une augmentation significative pour les mâles du groupe (04) comparés au groupe (05), une diminution non significative des concentrations de glucose chez les mâles des deux groupes (02) et (03), une augmentation non significative pour les deux groupes (04) et (05) comparés au groupe témoin, et elles étaient perturbées non significativement entre les groupes traités. Une diminution significative chez les femelles du cinquième groupe et non significative pour les deux groupes (02) et (03) et une augmentation non significative pour le groupe (04) comparé au groupe témoin et une diminution significative pour le groupe (05) comparé au groupe (03). Une diminution non significative des concentrations des triglycérides chez les mâles des groupes (02), (04) et (05) ainsi que chez les femelles des deux groupes (02) et (04), tandis qu’une augmentation non significative pour les mâles du troisième groupe et les femelles des deux groupes (03) et (05) comparés à ces groupes témoins et une perturbation non significative entre les groupes traités. Une diminution non significative des concentrations de cholestérol chez les mâles du groupe (02) et une augmentation non significative pour les groupes (03), (04) et (05) comparés au groupe témoin et ses perturbations non significatives entre les groupes traités. Ainsi que ces diminutions pour les femelles des deux groupes (02) et (05) et ses augmentations pour les femelles des groupes (03) et (04) comparées au groupe témoin et sa diminution significative chez le groupe (03) comparé au groupe (05).